Students Vocabulary Mastery and Their Reading Comprehension at the Selected Private Junior High School in Airmadidi - Simanungkalit, Ate Gueen; Tombeng, Jenita E. (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2023)
This study aimed to assess the extent of students' command of vocabulary and their level of reading comprehension among 8th-grade students in a selected private junior high school. It also sought to determine whether a significant correlation existed between students' vocabulary mastery and their reading comprehension. The research followed a quantitative approach, employing descriptive and correlational methods. The study included a sample of 90 students selected through purposive sampling. Two tests were employed as research instruments, one assessing vocabulary mastery and the other measuring reading comprehension. Mean Score and Pearson Correlation Coefficient were used for data analysis. The findings of this study revealed the following: (a) Students exhibited a very low level of vocabulary mastery, suggesting a lack of proficiency in vocabulary; (b) The level of reading comprehension among students was also notably low, indicating a limited understanding of their reading material; (c) A significant relationship was identified between students' vocabulary mastery and their reading comprehension. This implies that a higher level of vocabulary mastery corresponds to improved reading comprehension. However, the correlation was observed to be weak, suggesting the possibility of other influential factors impacting reading comprehension.